Sistem Pendidikan Dayah Tradisional di Aceh - Nurainiah Nurainiah (2021)
Dayah is the earliest educational institution in the archipelago. In the context of Aceh, dayah is not only a center for Islamic education, but also as a very important center for da'wah and social empowerment. In modern life, even though the dayah has not lost its role and function as a forum or study of science, even though many modern educational institutions have sprung up. Dayah as a center of traditional education in Aceh still survives without having to abandon its unique characteristics. The uniqueness of dayah education to date is its consistent education system. The focus of the study is the yellow book text in bare Arabic (without shakal). The education system commonly used in recitation and studying standard books in the dayah is the teacher reading the book, translating, then explaining the intent and purpose, while the students listen and pay attention to the reading with full concentration. For mubtadi students, the teacher usually reads slowly and translates word for word literally, so that they are easy to respond to and understand. In addition, the education system developed is Muzakarah or Munablood, Majlis Ta`lim and Muhadharah. In general, there are similarities in all dayahs regarding the main subjects taught, such as knowledge of Islamic law (Fiqh Science), grammar (Nahwu and Neuroscience), Tawhid and interpretation. Dayah has four significant uses as a center of religious learning, a bulwark against forces against colonial penetration, an agent of development and as a school for the community.